Periodisasi Hukum Islam : (Meneropong Praktik Hukum Islam Pada Masa Awal Islam dan Realisasinya di Indonesia) - Amalina Zukhrufatul Bahriyah; Ahmad Mahrus; Moh. Mujibur Rohman (ASASI: Journal of Islamic Family Law, 2023)
This article is a conceptual study of the periodization of the development of Islamic law, starting from the time of the Prophet Muhammad who brought Islamic dogmatic teachings, continuing during the time of the Companions as the second holders of the relay of Islamic civilization. And then its development in the following period until the implementation of Islamic law which began to be contained in Indonesian law, as formal law. The problems studied are as follows: 1) What are the sources of Islamic law?, 2) What is the method of establishing Islamic law in the early period, friends and tabi'in?, 3) How is the implementation of Islamic law in Indonesian national law? The aim is to find out the most important sources of Islamic law. In addition, to find out the method of establishing Islamic law in the early period, companions and tabi'in, as well as its implementation in Indonesia. Based on the form of this research is normative research with library research data collection techniques. From the data obtained then developed with data analysis in the form of a flow-model.